Framing Biodegradable Issues in Selected Online Nigerian Newspapers: An Environmental Communication Study: Array - Ndinojuo, Ben-Collins Emeka (Acta Universitatis Danubius. Communicatio, 2020)
This inductive qualitative content analysis study analyzes the themes embedded in stories about biodegradable in five online Nigeria newspapers namely the Cable, the Guardian, Leadership, Premium Times and the Punch using discourse analysis. The aim of the study was to understand and uncover the themes used by journalists when reporting about biodegradables especially in relation to its adoption as one of the solutions to the problems associated with waste management and the environment generally. Agenda setting and framing theories served as the theoretical bedrocks that grounded the study. Data was collected over a five-month period between April 1, 2019 and August 30, 3019, with the consideration of June 5 each year celebrated as World Environment Day, data from two months prior and two months after can provide context into how newspapers reported about biodegradables within the backdrop of environmental coverage. Findings produced 12 news articles which aligned with the literature about the under reportage of the environment in Nigerian newspapers. The themes uncovered were; adaptation, adverse impacts, climate change, economic, legislation, mitigation, persuasion, political and pollution themes. The prevalent themes were pollution, legislation and mitigation themes. The study recommends the need for more coverage of biodegradables bearing in mind the benefits derivable from its adoption in waste management, power generation, job creation and a sustainable development for the earth’s environment and its inhabitants.